2020
DOI: 10.5829/ijee.2020.11.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of the Thermal Performance of a Metal Fired-wood Oven

Abstract: This work is devoted to the evaluation of the performance of a typical fired-wood oven commonly used in the rotisserie sector in Burkina Faso. The methodology used is based on the energy balance of the oven. For this purpose, 20 liters of water were heated up to 90 °C. The difference in water temperature at the start and at the end of the experiment makes it possible to calculate the amount of energy consumed by the load. The temperatures of the walls as well as that of the ambient were recorded to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In our previous work, we have shown that grilling equipment lost almost half of the fuel consumed mainly through the walls [20]. We have also shown that the energy efficiency of fired-wood ovens used in Burkina Faso is low (around 19%) [21]. This research is a continuation of these works, and aims to study and analyze the energy efficiency of a local gas roasting oven.…”
Section: Introductionmentioning
confidence: 85%
“…In our previous work, we have shown that grilling equipment lost almost half of the fuel consumed mainly through the walls [20]. We have also shown that the energy efficiency of fired-wood ovens used in Burkina Faso is low (around 19%) [21]. This research is a continuation of these works, and aims to study and analyze the energy efficiency of a local gas roasting oven.…”
Section: Introductionmentioning
confidence: 85%
“…The thermal efficiency (η CS ) of such ovens should be like that of conventional gas ovens. According to Igo et al (2020), the thermal efficiency of a metal fired-wood oven to heat 20 liters of water from 35 to 90°C was found to be of ~19%, about 55% of the energy consumed being lost by hot fumes and 26% dispersed through the oven walls. Alternatively, the specific consumption of two types (indirect and semi-direct) of bakery ovens resulted in 0.55 and 0.90 kg of wood used per kg of wheat flour baked, respectively (Manhiça et al 2012).…”
Section: Main Cooking Appliancesmentioning
confidence: 99%